Biocomposite Interference Screws in Anterior Cruciate Ligament Reconstruction: Osteoconductivity and Degradation - F. Alan Barber, M.D.; W.D. Dockery, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2020)
Purpose: To evaluate the long-term in vivo degradation of an amorphous stereoisomer combined with micro β-tricalcium phosphate poly levo (96%)/dextro (4%) lactide beta-tricalcium phosphate biocomposite interference screw. Methods: A study approved by the institutional review board of in vivo biologic behavior of the screw was initiated in 2011 using an anterior cruciate ligament (ACL) reconstruction model. Twenty patients undergoing bone–patellar tendon–bone ACL reconstruction fixed at the femur and tibia with these biocomposite screws followed at least 36 months were evaluated by physical, radiographic, and computed tomography (CT) evaluations. Lysholm, Tegner, Cincinnati, and International Knee Documentation Committee scores were obtained. CT Hounsfield unit (HU) data were obtained at the femoral and tibial screw and other bone sites. An ossification quality score (range 1-4) was used to determine osteoconductivity at the screw sites. Results: In total, 11 male and 9 female patients evaluated by CT scan and radiographs a mean of 41 months postsurgery (range, 37-51) showed bone plug healing to the tunnel wall and the screw replaced with calcified and nontrabecular material. Osteoconductivity was present in 34 of 40 tunnels (85%) and nearly complete or complete (type 3 or 4 ossification) in 10 of 40 (25%). Mean screw-site densities (femoral 239 HU; tibial 290 HU) were consistent with cancellous bone density. One positive pivot-shift test was found. Lysholm, Cincinnati, Tegner, and International Knee Documentation Committee activity scores improved from 46.9, 43.5, 1.9, and 1.7 preoperatively to 92, 90.2, 6.0, and 3.2 at follow-up, respectively. The average postoperative Single Assessment Numeric Evaluation score was 86 and mean KT-1000 arthrometer difference was 0.32 mm. Conclusions: The micro β-tricalcium phosphate poly levo (96%)/dextro (4%) lactide beta-tricalcium phosphate interference screw was replaced by calcified, nontrabecular material a mean of 42 months after implantation in a bone–patellar tendon–bone ACL reconstruction model. Osteoconductivity was confirmed. Level of Evidence: Level IV (therapeutic case series).